Utilization of Community Managed Irrigation Scheme in Bale Zone: The case of Agarfa Woreda, Oromia Regional State, South East Ethiopia - Abe Neme, Abdissa; Ndemo Okoyo, Erick (Madda Walabu University Journal of Equity in Sciences and Sustainable Development, 2019)
Despite the significant contributions of agriculture in the overall economy of Ethiopia, its productivity is very low. Many factors contribute to low productivity among them is the problem of moisture stress is a constrictions cited one. The responses to cope up with drought and hence to improve the status of productivity of the agriculture is to adopt some form of irrigation practice. However, developing large scale irrigation is a costly alternative, which may require large quantity of capital resources. Moreover, this is a difficult job to practice for the small scale resource poor Ethiopian farmers. The alternative, which may compromise the need for expanding irrigation and the capital shortage, is promoting community managed irrigation scheme. Therefore, the objective of this study was to assess the utilization of community managed irrigation scheme. The study was conducted in Agarfa district, Oromia National Regional State. A total of 118 farmers were conducted in the study area. The chi-square (x2 ) and t-test was used to analyze the independent dummy and continuous variables respectively. A binary logit model was applied to investigate the factors affecting farmers' participation in community managed irrigation scheme. A total of 13 explanatory variables were used out of which 10 variables were positively significant and one variable was negatively significant affecting the farmers' participation in community managed irrigation scheme utilization but, two variables were not significant. The findings of this study indicate that any effort in promoting and utilizing community managed irrigation scheme should recognize the socio-economic, household, institutional, technological characteristics and others factors for better use of community managed irrigation scheme. Finally the authors was recommended that the concerned bodies were gives special to promote seed money for households and facilitating market information for their production and also helps policy makers to come up with projects that can win the hearts and minds of the farmers.